Use of Prophylactic Indomethacin in Preterm Infants: A Systematic Review and Meta-Analysis - Al-matary, Abdulrahman; Abu Shaheen, Amani; Abozaid, Sameh (Frontiers in Pediatrics, 2022)
Background: Prophylactic indomethacin has been widely used as an effective intervention for reducing mortalities and morbidities in preterm infants including the cardiopulmonary and neurodevelopmental morbidities such as intraventricular hemorrhage (IVH), but many studies have reported contradictory outcomes regarding its significance. Therefore, we aim to systematically review and meta-analyze the data of prophylactic indomethacin on preterm infants. Methods: Our systematic search included the following databases: Pubmed, Google Scholar, Scopus, Web of Science, The New York Academy of Medicine (NYAM), Virtual health library (VHL), and the System for Information on Grey Literature in Europe (SIGLE) to include studies that assessed the use of prophylactic indomethacin in preterm infants until August 12, 2021. Results: The final list of our included studies is comprised of 23 randomized trials and cohort studies. Among all the studies outcomes, significant favorable outcome was lowering the rate of PDA, surgical PDA ligation (P< 0.001) and severe IVH (P= 0.008) while no significance was recorded with BPD, pulmonary hemorrhage, intraventricular hemorrhage, necrotizing enterocolitis, intestinal perforation, mortality, and length of hospital stay. Conclusion: Since the meta-analysis results regarding effectiveness of prophylactic indomethacin varied based on the study design particularly with regard to outcomes such as surgical PDA ligation and severe IVH, this warrants the need for more evidence regarding the effectiveness of prophylactic indomethacin in very low birth weight infants.